Uso de recursos tróficos por Melipona quadrifasciata Lepeletier. 1986 e Melipona asilvai Moure, 1971 (Himenoptera: Apidae: Meliponini) no Alto Sertão Sergipano - Schettino, Sofia Cerqueira (2013)
This work had purposed to know the melissoflora visited by Melipona quadrifasciata and Melipona asilvai in the area of the forest fragment of Caatinga, situated in the city Poço Redondo, Sergipe, Brazil. Aiming at provide information that may contribute to the proper handling of the native bees. The study was developed in the period between March and November of the 2012, in Conservation Unidend Monumento Natural Grota do Angico . Observations in colonies bees and Monthly collections were made in the flowering plants, to verify the polen and prepare exsiccates, respectively. An amount of 71 species of plants in 47 families, which can be used by cited bees were identified in the area, and the more important families were Asteraceae , Euphorbiaceae, Fabaceae, Malvaceae , Myrtaceae, and Verbenaceae . To identification the pollen types present in the pollen aliment reserves within the colonies of bees, were made monthly collects, and method of Ertdman used for making blades and sequently photographed pollen types. An amount 21 and 25 pollen types were found, spread in 13 plant families in honey and pollen samples. Through the pollen spectrum of the honey samples obtained monthly in the cited bees , were identified high values of niche overlap in periods of resource supply, being the pollen type of family Fabaceae classified as the dominant pollen in the most of studied samples and the more representative, other pollen types as occasional pollen. Concluing in area studied that coexiste and are specialists in the use of floral resources.